Evaluating high-tech industries' technological innovation capability and spatial pattern evolution characteristics: Evidence from China - Wenjuan Tu; Lixiang Zhang; Dongying Sun; Wenqing Mao (Journal of Innovation & Knowledge (JIK), 2023)
The development of high-tech industries in an open economy has become an inevitable requirement for all countries to enhance their competitive advantages and overall national strength. Technological innovation is a direct driving force for promoting high-tech industries' development. The technological innovation capability of China's high-tech industries over 2010-2019 was measured using factor analysis. Moreover, the spatial pattern and evolution characteristics of the technological innovation capability of high-tech industries were analyzed using the Moran index. The empirical results demonstrate that: (1) during the research period, the technological innovation capability of China's high-tech industries rose, but regional development was uncoordinated. Input-output and transformation guarantee capacities were the main factors influencing technological innovation. (2) Improvements in the technological innovation capability of China's high-tech industries were spread over the southeast coast to the central and southwest regions. The technological innovation capabilities of high-tech industries in different regions exhibited an evident spatial correlation. The spatial agglomeration distribution is relatively stable, mainly characterized by 'Low-Low' (L-L) agglomeration. This study offers managerial enlightenment for improving the technological innovation capability of high-tech industries to accelerate industrial development to the middle and high end of the global value chain.
Keywords: 650; Capability of high-tech industries; Factor analysis; Moran index; Spatial pattern; Technological innovation